The formation of health-related procrastination in patients with type-2 diabetes: a grounded theory research - Shareinia, Habib; Ghiyasvandian, Shahrzad; Rooddehghan, Zahra; Esteghamati, Alireza (Frontiers in Psychology, 2024)
Considering the adverse effects of procrastination on the care and treatment of patients with type-2 diabetes, examining the how, why, and contributing factors of procrastination in this group of patients through in-depth studies seems essential. This is a grounded theory research in which 28 participants were selected by theoretical purposive sampling from patients with type-2 diabetes, their families, and healthcare personnel. Data were collected through interviews, observations, field notes and memos. The data were analyzed using Corbin and Strauss approach (2015) and MAXQDA 2010 software. The data obtained were classified into seven main categories. Health-related procrastination in patients with type-2 diabetes began to form in the patients when they perceived the hardships of self-care as their main concern. The ominous shadow of the disease, the prison of family care, patient-related factors, health system shortfalls, sociocultural background, and the onslaught of the COVID-19 pandemic laid the groundwork for abandoning diabetes self-care. Patients tried to abandon their diabetes self-care by adopting strategies such as escaping the reality of the disease, self-medication and procrastination. Wavering health-related procrastination was identified as the central category of this research. The formation of health-related procrastination in patients with type-2 diabetes is a multidimensional process depending on the patients' background that consists of their interactivity with their family, the health system, and the society. The findings of this research can be used for the design, implementation and monitoring of treatment and care programs for these patients.